Family Support and Diet Compliance for Elderly Hypertension at Prolanis Semanding Tuban Health Center - Shovia Mei Sanggar Wati; Teresia Retna Puspitadewi; Yasin Wahyurianto; Binti Yunariyah (Science Techno Health Journal, 2024)
Indonesia is currently experiencing a double burden of disease, namely infectious and non-communicable diseases. One of the non-communicable diseases that is currently a priority in global health is hypertension, which is known as the silent killer disease. Success in controlling hypertension is greatly influenced by patient compliance in following a hypertension diet. Objective : The aim of this research is to determine the description of family support and diet compliance for elderly hypertension at PROLANIS Semanding Tuban Health Center. Method : The research design used descriptive research with a population of 40 elderly people who were hypertensive and actively participating in PROLANIS. The sampling technique used was total sampling. The research instrument used a family support and diet compliance questionnaire. Results : Based on the research results show that the majority of hypertensive elderly who actively participate in PROLANIS activities receive good support and most are in the fairly compliant category. Most of the elderly with good family support had fairly compliant diet compliance and the majority of elderly with poor family support have non-compliant diet compliance Discussion : Family support is very important to give to elderly people who experience hypertension. Having support for the elderly can lead to inner peace and happy fealings in the elderly. Apart from that, support has an impacton making it easier for elderly people o follow a hypertension diet, because this diet is a control method that does not cause side effects and is natural.